Impact of depression severity on quality of life and functional impairment: a comparative cross-sectional study - Sethi, Prasanta K.; Mahapatra, Jashobanta (International Journal Of Community Medicine And Public Health, 2026)
Background: Major depressive disorder (MDD) is a widespread health issue linked to high mortality rates, functional impairment, disability, increased healthcare expenses, reduced quality of life, and psychosocial dysfunction. Dysfunction in social participation, productivity, and sense of subjective well-being persists even after reduction in depressive symptoms. Achieving symptomatic remission is not enough in the treatment of depression, but also understanding, assessing functional impairment, and Quality of Life together with symptom severity should be a holistic approach for the treatment of depression. Methods: A cross-sectional comparative study design was used. 60 individuals with depression samples were collected based on the purposive sampling method from a tertiary care hospital. Another 60 samples were collected from the general population for the normal control group on the basis of inclusion and exclusion criteria. Results: There were significant differences found in all four domains of QoL between the experimental and control groups, where the normal control group outperformed in all four domains of QoL with higher mean scores than the experimental group. The global score of the experimental group in WHODAS varies significantly (p=0.00) from the control group. The experimental group has higher dysfunction (83.28±10.29) in comparison to the control group (59.50±9.54). Conclusions: Functional impairment and QoL functioning are significantly affected in persons with depression. Shifting focus from only depression symptoms severity to consideration of functional impairment and QoL functioning would be a holistic approach for depression assessment and management.